Polish ethnocultural landscape of Podillya: structure, use, protection of cultural heritage - Volovyk, Volodymyr; Lavryk, Oleksandr; Yatsentyuk, Yuriy; Maksiytov, Andrii (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Introduction. The study of the structure and features of the ethnocultural heritage functioning is an important scientific problem, which is especially important for the implementation of regional and national strategies for sustainable development and optimization of the quality of the country’s environment. It is also important to solve the problem of traditional natural resource management of Podillya as a part of Eastern Europe, where a retrospective polyethnic development vector was formed, which has manifested in the formation of the Polish ethnocultural heritage. Problem formulation. The importance of professional analysis of assessment and assessment of ethnocultural landscape resource potential is based on justification of its future effective use, particularly, in the design of a regional network of ethnocultural protected areas, which aligns with the concept of sustainable development of Ukraine. Analysis of recent research and publications. Eastern European geographers have been developing the concept of the ethnocultural landscape since the end of the XX century and the following directions have been formed: 1) ethnocultural landscape is analyzed as cultural landscape; 2) ethnocultural landscape in anthropogenic landscape studies; 3) protection of ethnocultural artifacts; 4) as a part of humanistic geography. Highlighting previously unsolved parts of the overall problem. These studies will make it possible to evaluate the degree of Polish ethnocultural heritage influence on tourism development in Eastern Europe. This will allow to development of practical recommendations for the preservation and use of ethnocultural heritage in modern socio-economic conditions, the implementation of targeted programs involving EU funds. Formulating the purpose of the paper. The study aims to study the problem field of individual components of regional ethnocultural landscape science, its theoretical and practical potential, and its use in solving problems of nature management, namely Polish ethnocultural landscapes and relevant cultural heritage. Presentation of the main research material. The general regularities of formation of the estate, fortification and industrial landscapes, their ethnocultural features, and features of management are allocated. Proposals for optimization and intensification of nature use of Polish ethnocultural landscapes through protection and museification (regional landscape parks, open-air museums) of Polish historical and cultural artifacts of the region have been formed. Polish ethnocultural landscapes of Podillya are analyzed as an object of ethnocultural tourism. Thus, they will preserve biodiversity, create a basis for a harmonious combination of environmental and educational activities with the opportunity to get acquainted with the Polish historical and cultural heritage of the region. Conclusions. The unification of Polish ethnocultural artifacts in the villages and small towns of the region contributes to the transformation of heritage into a tourist product, which leads to interest in the preservation of monuments, increases the number of visitors. Given the number and spatial distribution of Polish heritage sites in the region, the creation of a landscape cadastre is one of the top priorities in addressing their protection and monitoring. Ethnocultural objects of Polish origin are usually the core of the planning structure of small towns or villages in the region. When attracting funds from Polish and Ukrainian investors, a profit that will significantly exceed the invested funds is possible. Ethnocultural heritage is one of the priorities of international tourism in the world’s leading countries.